Exploring Distorted Thinking About Food and Dietary Misinformation in Nonclinical Samples: Instrument and Intervention Development and Validation - Monaghan, Genevieve (Université d'Ottawa / University of Ottawa, 2017)
Distorted thinking about food is common in both clinical and nonclinical populations from dieters to diabetics and eating disorder patients. This type of thinking is triggered by exposure to dieting culture (including related social media), familial dieting, and internalization of the thin ideal, among other factors. The consequences of distorted thinking about food include disordered eating, weight management problems, body dissatisfaction and many others. Despite these findings, distorted thinking about food in nonclinical samples remains poorly understood. Thus, the current research sought to investigate distorted thinking about food within a broad theoretical model that includes societal antecedents important to understanding the nature of this construct in the general population. This model, which is based on Cognitive Behaviour Therapy (CBT) and the Theory of Planned Behaviour (TPB; Ajzen, 1991), was investigated in two studies. The first study is a psychometric validation study of a tool designed to measure distorted thinking about food, the Calorie Catastrophizing Scale (CCS; Monaghan & Santor, 2017) as well as the tool designed to measure dietary misinformation, the Dietary Misinformation Questionnaire (DMQ; Monaghan & Santor, 2017). Results lend support for defining and measuring distorted thinking about food as a distinct construct in nonclinical individuals and suggest that dietary misinformation is an important antecedent to this type of thinking and unhealthy eating behaviours. The second study is a randomized controlled trial of a CBT- and TPB-based workshop intervention aimed at reducing these antecedents. Results show that this intervention led to a significant reduction in distorted thinking about food, dietary misinformation, and other important clinical variables such as symptoms of eating pathology. These findings have a number of important implications for how subclinical eating problems are conceptualized, measured, and prevented.
Keywords: Distorted thinking about food; Dieting; Eating disorders; Cognitive distortions; Dietary misinformation; Nonclinical sample